1984
DOI: 10.1055/s-2007-1017419
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride - An Open Clinical Study of a New Benzamide in Schizophrenic Patients

Abstract: In pharmacological screening amisulpride produces no catalepsy, no inhibition of stereotypic movements, yet a blockade of drug-induced vomiting. During an open clinical trial lasting 4 weeks, 14 patients (13 schizophrenics) were treated with the compound. The (BPRS-) syndromes anxiety/depression, thought disorder, activity, hostility and the global score showed significant improvement. With the AMDP system significant changes were seen in the paranoid-hallucinatory, manic, depressive and hostility syndromes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…When the two medications were compared, the amisulpride group showed a beUer performance with respect to the antidepressant efTects. This result correlates with the results of numerous previous studies (Klein et al , 1983;Mann et al , 1984;Ziegler and Jesau, 1984). In addition, the amisulpride group revealed reduced manifestations of extrapyramidal side-efTects as measured by the Simpson and Webster scales.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When the two medications were compared, the amisulpride group showed a beUer performance with respect to the antidepressant efTects. This result correlates with the results of numerous previous studies (Klein et al , 1983;Mann et al , 1984;Ziegler and Jesau, 1984). In addition, the amisulpride group revealed reduced manifestations of extrapyramidal side-efTects as measured by the Simpson and Webster scales.…”
Section: Discussionsupporting
confidence: 93%
“…Haloperidol appeared to generate more extrapyramidal side-effects. Mann et al (1984) examined amisulpride in an open clinical study of 13 schizophrenics. On the whole, amisulpride treatment proved effective: taken together, the BPRS syndrome-scores such as anxiety-depression, thought disturbance, activation or hostility showed significant improveme nt.…”
Section: Introductionmentioning
confidence: 99%
“…44,47,50,108,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131] ( Table 3) Twenty-five articles were identified that reported relevant data. One of these 101 was also reported in Table 1 because overt violence was an outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…Amisulpride has been shown to be an effective and safe atypical antipsychotic drug [13,27,28,33,39] and exhibits a unique pharmacological profile, which is characterized by a predominant interaction with D3/D2-dopamine receptors [41]. Amelioration of negative symptoms, even at a low dose (100 mg/day) [40], and absence of weight gain belong to the important advantages of this substance [26].…”
Section: Original Papermentioning
confidence: 99%